ASIS IDOL sebagai Model Pengabdian kepada Masyarakat dalam Penguatan Karakter, Kepemimpinan, dan Kepedulian Sosial Peserta Didik - Dewiana Novitasari; Temmy Setiawan; Masduki Asbari; Wakhida Nurhayati; Firdaus Putra (Yayasan Aya Sophia Indonesia, 2026)
This community service program aims to implement the role of lecturers in supporting educational institutions through the ASIS IDOL (Aya Sophia Islamic School Inspiration and Development of Leadership) selection program. The program serves as a platform for character building, leadership development, literacy, environmental awareness, anti-bullying, and local cultural preservation among elementary and secondary students. Using a participatory-educational approach, the activities involved thematic selection, student presentations, reflective dialogue, and rubric-based character assessment. The results indicate increased student awareness of personal responsibility, exemplary leadership, and internalization of Islamic and social values in daily life. ASIS IDOL proves to be an effective collaborative PKM model between lecturers, schools, and the community in strengthening character education ecosystems.